Development and evaluation of an educational fantasy comic for geometry transformation learning: enhancing junior high school students’ mathematical reasoning and self-esteem - Wanda Nugroho Yanuarto; Faizal Abdul Hafizh (CV. FOUNDAE, 2026)
Background: Indonesian students’ mathematical literacy remains low, as evidenced by the 2022 PISA results, which indicate difficulties in understanding concepts and solving contextual problems. Geometry transformation topics require strong abstract thinking and visualization skills; however, conventional instruction often emphasizes memorization rather than conceptual understanding. In addition, students’ low self-esteem further hinders their engagement and achievement in mathematics learning. Therefore, innovative instructional media are needed to support both cognitive and affective learning outcomes. Aims: This study aims to develop an educational fantasy comic as a learning medium for geometry transformation and to examine its effectiveness in enhancing junior high school students’ mathematical reasoning and self-esteem. Method: This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The participants were junior high school students. Data were collected through expert validation, questionnaires, mathematical reasoning tests, and self-esteem scales, and analyzed using descriptive quantitative and qualitative techniques. Results: The validation results indicated that the developed comic achieved a score of 82.73%, categorized as “very valid.” The practicality test showed an average score of 4.12 (82.42%), indicating that the comic was highly practical for classroom use. Furthermore, the effectiveness results demonstrated that students who learned using the educational fantasy comic exhibited better mathematical reasoning skills and higher self-esteem compared to those receiving conventional instruction. Conclusion: The educational fantasy comic is a valid, practical, and effective learning medium that enhances students’ mathematical reasoning and self-esteem, offering an engaging and meaningful alternative for geometry transformation learning.